Implementasi Pendidikan Inklusif Di SMKN 2 Malang - Desy Rismayanti; Endang Poerwanti (Jurnal Kebijakan dan Pengembangan Pendidikan, 2019)
Abstract: The development of 21st-century education has provided opportunities for persons with disabilities to obtain the same education as students in general. The study aims to find out 1) the implementation of inclusive education which includes the acceptance, planning, implementation, and evaluation of students; 2) supporting and inhibiting factors for the implementation of inclusive schools, and 3) positive and negative impacts of the implementation of inclusive schools in Vocational High School 2 Malang. This research uses qualitative research. The results showed that 1) the implementation was good in terms of acceptance, planning, implementation, and evaluation, which was followed by students with special needs with autism, mentally disabled, ADHD, slow learner, deaf, and dual disability (more disability). 2) Internal and external supporting factors are the collaboration of various inclusive education actors, the government, parents or guardians of students, communities around the school, as well as special assistant teachers. Internal and external inhibiting factors, the lack of infrastructure assistance from the government. 3) The positive impact of the implementation of inclusive education in Vocational High School 2 Malang is the support of all parties to inclusive education, for the negative impact of this study in the inhibiting factor, namely the lack of infrastructure assistance from the government. Researchers suggest that schools should always send letters to the government regarding infrastructure facilities so that the government can be responsive in helping with this. It can also find sponsors through CSR (Corporate Social Responsibility), self-funding from parents of parents, and raising public funds.Keywords: Implementation, Inclusive Education, The Child with Special Needed Abstrak: Perkembangan pendidikan abad 21 ini telah memberikan kesempatan kepada para penyandang difabel untuk memperoleh pendidikan yang sama dengan siswa pada umumnya.Tujuan penelitian ini yaitu untuk mengetahui a) implementasi pendidikan inklusif berjalan yang meliputi penerimaan, perencanaan, pelaksanaan, dan evaluasi bagi peserta didik; b) faktor pendukung dan penghambat implementasi sekolah inklusif; serta c) dampak positif dan negatif dari implementasi sekolah inklusif di SMKN 2 Malang. Penelitian ini menggunakan jenis penelitiankualitatif. Hasil penelitian menunjukkan bahwa 1) pelaksanaan sudah baik dalam hal penerimaan, perencanaan, pelaksanaan, serta evaluasi, yang diikuti oleh peserta didik berkebutuhan khusus dengan ketunaanautis, tuna grahita, ADHD, slow learner, tuna rungu, serta ketunaan ganda (lebih ketunaannya). 2) Faktor pendukung internal dan eksternal adanya kolaborasi dari berbagai pelaku pendidikan inklusif, pemerintah, orang tua wali murid, masyarakat sekitar sekolah, serta para guru pendamping khusus. Faktor penghambat internal dan eksternal, minimnya bantuan sarana prasarana dari pemerintah. 3) Dampak positif dari implementasi pendidikan inklusif di SMK Negeri 2 Malang adanya dukungan dari semua pihak pelaku pendidikan inklusif, untuk dampak negatif penelitian ini dalam faktor penghambat yaitu minimnya bantuan sarana prasarana dari pemerintah. Saran peneliti, sebaiknya sekolah selalu mengirim surat untuk pemerintah dalam hal bantuan sarana prasarana agar pemerintah bisa cepat tanggap dalam membantu dalam hal ini. Bisa juga mencari sponsor melalui CSR (Corporate Social Responsibility), swadana dari orang tua wali murid, dan penggalangan dari dana masyarakat.Kata kunci: Implementasi, Pendidikan Inklusif, Anak Berkebutuhan Khusus